Herpes encephalitis and hepatitis in pregnancy: A case report and literature review. (June 2022) - McCarthy, Claire M; Conlon, Caroline; Kennelly, Maria; Drew, Richard; Stewart, Stephen; Geary, Michael P
We present the case of a healthy nulliparous woman who presented with persistent fever, proteinuria and elevated transaminases at 33 weeks' gestation. Following initial treatment for suspected chorioamnionitis and potential pre-eclampsia, she had a caesarean section delivering a healthy male infant. However, on her third post-operative day, she developed neurological symptoms and accompanying severe sepsis, necessitating inotropic support and transfer to a higher level of care. A comprehensive work-up revealed herpes simplex Virus-2 (HSV-2) in serum and cerebrospinal fluid. Abdominal imaging was suggestive of accompanying hepatitis with micro-abscesses. This lady recovered well following intravenous acyclovir for 14 days. Her infant was not affected and was discharged home with his mother. Herpes simplex encephalitis and hepatitis associated with HSV-2 have been described three times previously in pregnancy. We delineate the diagnostic challenges that rare conditions such as this pose and emphasise the importance of multi-disciplinary care in managing complicated medical conditions in pregnancy.